Cyclic testing and parametric analyses of the fabricated steel frames infilled with autoclaved aerated concrete panels. Issue 4 (April 2017) - Zhenggang, Cao; Peng, Du; Feng, Fan; Ming, Fang
The influence of autoclaved aerated concrete panels on the mechanical properties of fabricated steel frames was experimentally investigated. Two fabricated steel frame specimens, which were with and without autoclaved aerated concrete panels, respectively, were tested under reversed cyclic loads. They were 1/2-scale, two-storey, and single-bay steel frames that were assembled by bolted beam-height adjustable steel beam-to-column connections. The effect of autoclaved aerated concrete panel dimensions on the mechanical behavior of infilled frames was also parametrically analyzed with the proposed numerical models which were verified on the basis of experimental data. The results indicate that the fabricated steel frames, assembled by beam-height adjustable connections, could behave in a ductile manner with sufficient stiffness and strength under cyclic loads; compared with bare steel frames, autoclaved aerated concrete panels could postpone the failure of structures and increase their initial stiffness, peak load, and energy dissipation capacity; moreover, the geometric details of autoclaved aerated concrete panels could significantly change the mechanical properties of infilled steel frames.